Fine ablation with depth control of 25-nm resolution and morphologies irradiated by femtosecond laser pulses via beam shaping - Shin, Young-Gwan; Choi, Junha; Cho, Sung-Hak (Applied physics. A, Materials science & processing, 2023)
Recently, the need for enhanced cutting tools to fabricate next-generation multilayer ceramic capacitors (MLCCs) and batteries has been identified. This is because existing cutting tools cause problems such as defects, burrs, and breaking of MLCCs when the MLCCs are cut using the existing cutting tools. Furthermore, the productivity of MLCCs should be improved. To overcome these problems, enhanced cutting tools should have sharper blade angles and thinner widths. Currently, a cutting tool with a thickness of tens of micrometers is used in the industry. Also, cutting tools made of cemented tungsten carbide are difficult to machine. Therefore, fine ablation technology is required for their application. Machining technology using femtosecond lasers has been studied to realize fine ablation. However, studies on the subject are limited. Therefore, we studied fine ablation using the beam-shaping technology. In this study, a femtosecond laser with a wavelength of 1030 nm, a maximum repetition rate of 200 kHz, and a maximum pulse energy of 1 mJ was used. Additionally, a slit-optic system was used to transform the laser beam with Gaussian energy distribution into the laser beam with a quasi-flat top energy distribution. We demonstrated a machining depth resolution of 25 nm for cemented tungsten carbides using a femtosecond laser with a fluence of 0.32 J/cm 2 .